Interelasi Spiritualitas Jawa dan Hadis Nabi; Analisis Nilai-Nilai Hadis dalam Kidung ‎Wahyu Kolosebo - Fahimah, Rif'iyatul (Jurnal Ulunnuha, 2024)
The assumption circulates that Javanese spirituality is not connected to the teachings of Islam due to its association with mystical, supernatural, superstitious, occult, and mythical practices. However, until today, Javanese spirituality influenced by Islam continues to be preserved, as reflected in one of the songs by Sri Narendra Kalasebo titled "Kidung Wahyu Kolosebo". This article is a literature review conducted using a qualitative approach with descriptive analysis and content analysis techniques. The author presents research data to achieve the research objective, which is to understand the correlation between Javanese spirituality and the sayings of Prophet Muhammad, particularly by analyzing the values of the sayings within the song "Wahyu Kolosebo". Corresponds to relevant sayings, highlighting the undeniable connection between Javanese spirituality and the sayings of Prophet Muhammad, despite their inherent differences. Keywords: Javanese spirituality, Hadith, "Kidung Wahyu Kolosebo".